Smartboard for surfing - Diogo Faria Correia (2020)
The Internet of Things has democratized the use of sports' monitoring devices. The majority of these devices, available on the market, are targeted to the fitness practice creating the necessity of having different solutions for different sports. This work focuses on the development of a low-profile surf monitoring device capable of acquiring the required data for an existing algorithm developed by Fraunhofer Portugal. The resulting system should support long periods inside the water (low-power and waterproofed) without interfering with the athlete's performance (low-profile) and be able of transmitting the acquired data for an external device. Due to project's requirements, some of the technologies were already selected (microcontroller, gyroscope, magnetometer, accelerometer and GNSS module). However other technologies such as: the wireless communication system, storage method and power system needed to be selected. For the first, the system data throughput was estimated and the technology with the best relation throughput vs. power consumption was selected. To select the storage method, a survey was conducted to estimate the relation between each technology's price and data size. To select the power system, two studies were conducted in order to infer the hypothesis of supplying the system with photovoltaic cells, increasing the autonomy during a surf session: a power consumption study to estimate the system's power requirements and a solar irradiance study to predict the required area of photovoltaic cells. In order to determine the impact of having epoxy resin, commonly used to cover surf boards, some tests were conducted by applying this resin over the cells and measuring the output power.